The Importance of Local Opera Inheritors’ Identity in Their Artistic Creation: A Case Study of Chang Deng Opera in Leye, Guangxi - LIANG, FENGZHI (Pacific International Journal, 2024)
This study explores the critical role of identity in the artistic creation of Chang Deng Opera inheritors in Leye County, Guangxi. With a history spanning over 300 years, Chang Deng Opera is a unique local opera form that has evolved from folk traditions deeply rooted in the cultural and geographical context of the region. Utilizing a qualitative research approach, this study chooses semi-structured interviews with the inheritors from County. The findings highlight the significant influence of cultural heritage on personal identity and how this identity, in turn, shapes artistic creativity. Inheritors’ narratives reveal a deep emotional connection to their art, driving their commitment to preserving and innovating within the tradition. This study also compares Chang Deng Opera with other local opera forms, illustrating its distinct characteristics and contributions to the broader landscape of Chinese traditional arts. The implications for the preservation of traditional arts emphasize the necessity of engaging with the cultural and emotional dimensions of these art forms, ensuring their continued relevance and vitality.